Penerapan Sistem Pendukung Keputusan Untuk Rekomendasi Pemilihan VGA Terbaik 2024 Menggunakan Metode Weighted Product - Krisna Bima Bagus Saputra; Arita Witanti (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
In recent years, the development of VGA technology has advanced rapidly, with various brands and models offering diverse specifications and features. Modern VGA cards are not only used for basic needs such as displaying images but also for more complex tasks like 3D graphics rendering, video editing, and gaming. This advancement provides consumers with many choices but also creates confusion in determining the VGA that best fits their needs and budget. Making the right decision in choosing a VGA becomes a particular challenge, especially for users without in-depth knowledge of technical specifications and VGA performance. Incorrect choices can lead to suboptimal computer performance, inefficient power usage, and user dissatisfaction. To address this issue, researchers have developed a web-based decision support system that recommends the best VGA selection using the Weighted Product method. This system performs calculations on 30 VGA data points based on 5 established criteria: price, memory capacity (VRAM), graphic resolution, power consumption, and number of supported monitors. The calculations reveal that the AMD Radeon RX 7900 XTX achieved the highest recommendation score at RSC Computer Store in Klaten, with a score of 0.058507812, followed by the NVIDIA GeForce RTX 4080 with a score of 0.058243034, and the AMD Radeon RX 7900 XT with a score of 0.055677317. This system demonstrates its effectiveness in providing accurate and beneficial recommendations for consumers in selecting a VGA according to their preferences and needs.